Development of an Energy-Efficient Flipbook Based on Project-Based Learning (PjBL) to Strengthen the Profile of Pancasila Students and Preserve Local Wisdom in Elementary Schools - Wulandari, Sisca; Istiyono, Yogi Priyo; Anjuli, Angel Putri; Nursabila, Afelia Ala (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2025)
Project-Based Learning (PjBL) is a recommended instructional model to strengthen the Pancasila Student Profile and preserve local wisdom. PjBL prioritizes student activities aimed at producing outputs through skills such as inquiry, analysis, creation, and presentation. These outputs are based on real-life experiences. This study employed the ADDIE methodology, encompassing analysis, design, development, implementation, and evaluation phases. Both quantitative and qualitative data were analyzed. The PjBL-based flipbook for elementary school was evaluated as highly valid, receiving validity scores of 85% from content experts, 90% from media experts, and 80% from teachers, all within the highly valid category. Individual tests, small group tests, and field tests showed high validity rates with percentages of 90%, 100%, and 90%, respectively. Based on these assessment findings, it can be concluded that the product demonstrates high validity, practicality, and effectiveness in reinforcing the Pancasila Student Profile and preserving local wisdom.